TopSeal-Dentine Interface After two Obturation Techniques: Lateral Condensation and Thermoplastified/Thermosoftened Technique. A SEM Study - Guzmán de Sousa, Bennys; Pontificia Universidad Javeriana (Editorial Pontificia Universidad Javeriana, 2010)
Background: Vertical condensation (VC) endodontic systems have improved results of endodontic treatment when compared to lateral condensation (LC). They improve the diffusion and adaptability of the sealer cement (SC) and the gutta-percha (GP), in order to obtain a hermetic sealing and ensure the lack of cracks in the sealer material-dentine interface. However, it has not been established whether the application of heat may or not alter the sealer cement-dentine interface (SCDI). Objective: Compare the SCDI at different distances from the root apex, when using two obturation techniques, vertical (TopSeal®) and lateral. Methods: An in vitro experimental study with scanning electron microscopy (SEM) was carried out. Canals of 40 recently extracted single-root premolars were endodontically prepared with the same instrumentation technique. 20 of them were sealed with LC and TopSeal® and the other 20 were sealed with VC and TopSeal®. The specimens were then cut at 1 mm, 4 mm, and 8 mm from the root apex and observed under SEM. Results: Statistically significant differences were observed in the SCDI of teeth sealed with VC compared to those sealed with LC (p